2021
DOI: 10.4103/jrms.jrms_585_20
|View full text |Cite
|
Sign up to set email alerts
|

Skin and metabolic syndrome

Abstract: Metabolic syndrome (MeTS) is a well-known health-related problem with several end-organ damages and the resulted side effects such as rising in the blood glucose and lipid and blood pressure. Although MeTS might show several skin symptoms such as acanthosis nigricans, skin tags, acne, and androgenic alopecia, it could also be implicated in the pathophysiology of numerous dermatologic disorders. Furthermore, some dermatologic drugs might be implicated in the incidence or exacerbation of MeTS. Consequently, MeTS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 97 publications
(98 reference statements)
0
9
0
Order By: Relevance
“…Taking into account the growing prevalence of MetS as a significant health issue worldwide, there has been an increase in the number of studies assessing the relationship between MetS and skin disease in recent years 7 . MetS is a well‐known NCD identified by its side effects, such as end‐organ damage, elevated levels of glucose and blood lipids, as well as high BP 50 . This makes patients susceptible to type 2 diabetes and cardiovascular diseases, such as atherosclerosis and hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Taking into account the growing prevalence of MetS as a significant health issue worldwide, there has been an increase in the number of studies assessing the relationship between MetS and skin disease in recent years 7 . MetS is a well‐known NCD identified by its side effects, such as end‐organ damage, elevated levels of glucose and blood lipids, as well as high BP 50 . This makes patients susceptible to type 2 diabetes and cardiovascular diseases, such as atherosclerosis and hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…A study directly elucidated that diabetes was significantly associated with FPHL frontal alopecia ( P = 0.023) [ 38 ]. Insulin resistance might induce a hormonal imbalance in circulating androgens, which may explain the relationship between diabetes and AGA [ 39 ]. A prospective study in Taiwan concluded that moderate-to-severe AGA was an independent predictor of diabetes [ 40 ].…”
Section: Endocrine Diseasementioning
confidence: 99%
“…[11][12][13] Obesity in the form of visceral adipose increases the blood glucose level and contributes to insulin resistance, which can influence the level of circulating androgens and hence acne development. [9][10][11][12][13] Adipose tissue itself also contains both estrogen and androgen receptors. 9,12,13 Studies have shown that patients with acne who consume food that has a lower glycemic load tend to have less lesions than those who consume diets with a higher glycemic load.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13] Adipose tissue itself also contains both estrogen and androgen receptors. 9,12,13 Studies have shown that patients with acne who consume food that has a lower glycemic load tend to have less lesions than those who consume diets with a higher glycemic load. 10 Weight loss has been shown to improve factors that contribute to both the inflammatory and endogenous factors that contribute to acne.…”
Section: Introductionmentioning
confidence: 99%